THE USE OF E-PEN AND COMPUTER BY THE ENGLISH TEACHER AT ELEMENTARY SCHOOL - Erni Nadia (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2019)
This research uses descriptive method. The aimed is to know the use of E-Pen and Computer by the English teacher at Elementary School. The data collection and data processing procedure was done using class observation, interview the teacher and documentation. The analysis was done by comparing the theories and the factual data found. The result found that during teaching and learning activities, teacher used computer in pre-activity to stimulate students’ attention in the beginning of the lesson. The function of computer is to show the video, audio/song and Microsoft power Point/slides, then reflected into whiteboard. The teacher used E-Pen in whilst activity, it was very helpful to make the students knows right pronunciation from the native speakers. The teacher’s way when used the E-Pen by touching it to the textbook then the E-Pen will speak it out and was heard by whole class clearly. Using E-Pen and Computer in teaching and learning process is satisfying. By using E-Pen and Computer, the students can master vocabulary and pronunciation. Using E-Pen and Computer in the classroom makes the class more interesting, more active, more motivated in learning and easier to grasp the lesson.